Explaining the impact of consumer religiosity, perceived risk and moral potency on purchase intentions. (July 2020) - Mortimer, Gary; Fazal-e-Hasan, Syed Muhammad; Grimmer, Martin; Grimmer, Louise
Abstract: The role of religion has been overlooked as an antecedent to risk perception, as has moral potency, when purchasing religiously sensitive products. The aim of this study is to demonstrate how perceived risk and moral potency explain the impact of shopper religiosity on purchasing religiously-questionable products from retailers. A conceptual model was tested on a sample of 271 respondents, elucidating the complex relationships between religiosity, social and psychological risk, moral potency and purchase intention. The model offers a strong psychological explanation of how a shopper's religion may increase their perceptions of risk and personal responsibility, confidence and courage, which subsequently impact purchase intentions. Retail managers may choose to implement this model to better predict shopper adoption behaviour of new religiously-questionable products. The model allows for future empirical examinations across multiple shopping contexts and may be employed to estimate levels of demand for new products based on the extent of religiosity, moral potency and risk.